Object Detection for Katsuwonus Pelamis based on ExeML ModelArts - Suryadiputra Liawatimena; Franz Adeta Junior; Derrell Rizqullah Hasan (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Indonesia is one of the countries with the largest export of fish commodities in the world. Katsuwonus Pelamis (Cakalang or Tuna Skipjack) and Euthynnus Affinis (Tongkol or Mackarel tuna) have high economic value and are Indonesia's most significant foreign exchange earners. There is a need to measure the length and weight of the caught Katsuwonus Pelamis to help the Ministry of Marine Affairs and Fisheries achieve sustainable fishing. The existing method still relies on traditional data recorded by the person conducting the survey, and the calculations are frequently inaccurate. This paper proposed an object detection for Katsuwonus Pelamis based on ExeML ModelArts. The 4.000 images were divided into 80:20 for the training and validation set. The overall average errors are 5.19% for the estimated length of the fish and 21.98% for the estimated weight.